2017
DOI: 10.1097/ncc.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

Using Perceived Self-efficacy to Improve Fatigue and Fatigability In Postsurgical Lung Cancer Patients

Abstract: Background Fatigue remains a prevalent and debilitating symptom in persons with non-small cell lung cancer (NSCLC). Exercise has been shown to be effective in reducing fatigue; yet interventions are limited for post-surgical NSCLC patients. To date, while surgery is offered as a standard curative treatment for NSCLC, no formal guidelines exist for post-surgical rehabilitation. Objective This study focuses on the design and testing of a post-surgical intervention for NSCLC patients to promote perceived self-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
138
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(139 citation statements)
references
References 49 publications
1
138
0
Order By: Relevance
“…Cancer patients with lower self-efficacy are inclined to experience more fatigue (Johansson, Brink, Cliffordson, & Axelsson, 2018). Therefore, self-management is implemented in studies and proven as an effective treatment for improving self-efficacy, CRF and QOL (Foster et al, 2016;Hoffman et al, 2017) by developing patients' selfmanagement theories and skills through role, medical and emotional management tasks (Medicine, 2004). However, traditional self-management support is limited by the availability of medical professionals, time, money, facilities, and setting resources (Stubblefield, 2017), insufficient to meet the needs of patients, such as ongoing follow-up support (Ostby, Armer, Smith, & Stewart, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer patients with lower self-efficacy are inclined to experience more fatigue (Johansson, Brink, Cliffordson, & Axelsson, 2018). Therefore, self-management is implemented in studies and proven as an effective treatment for improving self-efficacy, CRF and QOL (Foster et al, 2016;Hoffman et al, 2017) by developing patients' selfmanagement theories and skills through role, medical and emotional management tasks (Medicine, 2004). However, traditional self-management support is limited by the availability of medical professionals, time, money, facilities, and setting resources (Stubblefield, 2017), insufficient to meet the needs of patients, such as ongoing follow-up support (Ostby, Armer, Smith, & Stewart, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between self-efficacy and quality of life has also been identified in some studies (Kiaei et al 2016;Mudrak et al 2016;Yeung & Lu 2014). In another study, the positive effect of self-efficacy on postsurgical complications in lung cancer was addressed (Hoffman et al 2017). Increasing self-efficacy in the caregivers of hospitalized cancer patients has been proven to reduce cancer symptoms as well as caregivers' stress for their practice (Hendrix et al 2016).…”
Section: Discussionmentioning
confidence: 84%
“… 19 Of the remaining 21 studies, 2 were editorials 20 , 21 and 5 were published as abstracts 22 – 26 and therefore data were not complete. Regarding these abstracts, two 22 , 26 were excluded because they were already included as full texts 27 , 28 in our initial bibliographic research. Concerning the three remaining abstracts, we contacted the corresponding authors in order to obtain complete data.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, six RCTs were included in this review. 8 , 25 , 27 , 37 39 The flow chart representing selection process of studies is reported in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation